Enteroscopy in children. Issue 7 (1st August 2018) - Di Nardo, Giovanni; Calabrese, Carlo; Conti Nibali, Roberto; De Matteis, Arianna; Casciani, Emanuele; Martemucci, Luigi; Pagliaro, Giuseppe; Pagano, Nico
Abstract : Introduction: Device‐assisted enteroscopy is a new endoscopic technique for the evaluation of small bowel in adults and children. Data in pediatric population are limited. This review aims to identify diagnostic and therapeutic benefits of enteroscopy in children. Methods: We have analysed paediatric literature on device‐assisted enteroscopy focusing on indications, technical aspects and complications, with attention given to adult publications that may be applicable to the paediatric population. Results: Obscure gastrointestinal bleeding, Crohn's disease and small bowel polyps are the main indications of enteroscopy in children. Device‐assisted enteroscopy has high diagnostic yield for the main paediatric indications, but MR‐enterography and capsule endoscopy should be used beforehand in diagnostic work‐up to better identify candidates for enteroscopy and to improve its diagnostic and therapeutic yield. Major complications are rare and mostly related to therapeutic procedures. Conclusion: Despite limited data in the paediatric population, device‐assisted enteroscopy represents a useful and safe endoscopic technique in children. Its use, combined with MR‐enterography and capsule endoscopy, allows identification and treatment of many of the small bowel paediatric diseases with a low risk of complications.